Pharmacological Effects of Peganum harmala Seeds Extract on Isolated Rat Uterus: Effects of Peganum harmala on rat uterus - Fathiazad, Fatemeh; Azarmi, Yadollah; Khodaie, Laleh (Iranian Journal of Pharmaceutical Sciences, 2006)
The effects of hydroalcoholic extract of Peganum harmala seeds (EPS) on spontaneous rhythmic contractions of isolated rat uterine was investigated in this study. EPS was tested on the isolated uterus and endometrium free (i.e. stripped myometrium) preparations. EPS was found to exhibit significant spontaneous contractions of the uterus and stripped myometrium relative to the solvent control. After recording the pattern of uterus tissue spontaneous motility, in order to determine mechanism of EPS pharmacological effects, atropine, indomethacin, or prazocin was added into the organ baths. Pretreatment with atropine (70 nM) in both the whole uterus and in the stripped myometrium preparations had no effects on the response to cumulative dosage of EPS. Calcium-free solution decreased the uterus contractions. In calcium dose-response curves, EPS in some concentrations produced uterotonic effect in calcium-free solution in the presence of KCl. This finding showed that EPS may increase calcium influx through voltage-dependant calcium channels.